Enhancing the ocean carbon sink capacity of Shandong province, China, under the “dual carbon” goal - Mao, Zhengkai; Liu, Huirong; Zhang, Zhijun (Frontiers in Marine Science, 2023)
The ocean is a key component of the global carbon cycle. As climate change becomes increasingly severe, enhancing the ocean's carbon sink capacity is of great significance to achieving the "dual carbon" goal for China. As a major maritime province, Shandong is in an advantageous position to utilize the ocean to respond to climate change and achieve the national goals of carbon peaking and carbon neutrality. Focusing on consolidating and enhancing ocean carbon sink capabilities, Shandong needs to formulate a clear timetable and roadmap to promote blue carbon technology research and development, actively cultivate a blue carbon trading market, and tap the inner potential of ocean carbon sink. Shandong should also strengthen international cooperation to jointly construct a carbonneutral global community.